TRANSFORMASI RELIEF CANDI PRAMBANAN DALAM KARYA TUBUH RITUS TUBUH OLEH ANGGONO KUSUMO WIBOWO - Siska Dwi Purwanti; Daryono Daryono (Institut Seni Indonesia Surakarta, 2020)
Transformation is a process of changing form, nature, and so on into new forms without leaving the values that existed in the previous culture. The process of transformation always produces elements of novelty, both in terms of style, taste, and meaning even at different levels of change. Transformation in art does not only occur in similar arts. Ancient relics, for example, as one form of art can be a starting point to be interpreted into visual expression in contemporary art, including dance. Tubuh Ritus Tubuh is one of the dance works which is a form of transformation of the Prambanan Temple relief. This study tries to uncover the allegations of the transformation of the Prambanan temple reliefs that can be observed on Tubuh Ritus Tubuh dance presentation. The problem of transformation is examined using the theory of change expressed by Lorens Bagus. The participatory research method carried out by the author is able to uncover the form of transformation found in certain parts of the dance presentation. Keywords: transformation, relief, Prambanan Temple, Tubuh Ritus Tubuh.